The Effect of Using English Song on Spotify Application on Students’ Listening Ability at SMK Muhammadiyah 1 Pekanbaru - Wahyuni, Elga Sri; Fauzana, Riri (Journal of English and Arabic Language Teaching, 2024)
This research aims to test whether there is a difference between before and after the use of Song on Spotify Application, this research was conducted using pre-experimental method with a total sample of 19 students, and the research was conducted in class 12 AKL.The sampling in this study using purposive sampling. The instrument in this study was a fill in the blank test and consisted of 20 questions. The results showed a significant difference between before and after the use of word square model, researcher used the paired sample T-test test through the SPSS 20 program with a significance value of 0.001, lower than 0.005 and researchers also used the eta square formula with a result of 0.54.